Alcohol, Violence and Injury-Induced Mortality: Evidence from a Modern-Day Prohibition - Kai Barron; Charles D.H. Parry; Debbie Bradshaw; Rob Dorrington; Pam Groenewald; Ria Laubscher; Richard Matzopoulos (The Review of Economics and Statistics, 2022)
This paper evaluates the impact of a sudden and unexpected nation-wide alcohol sales ban in South Africa. We find that this policy causally reduced injury-induced mortality in the country by at least 14%. We argue that this estimate constitutes a lower bound on the true impact of alcohol on injury-induced mortality. We also document a sharp drop in violent crimes, indicating a tight link between alcohol and aggressive behavior in society. Our results underscore the severe harm that alcohol can cause and point towards a role for policy measures that target the heaviest drinkers in society.
Keywords: I18; I12; K42; 330; alcohol; mortality; economics; health; crime; South Africa; COVID-19; violence